The Moderating Role of Self-Regulation in the Relationship between Social Support and Academic Resilience among Indonesian Students - Estalita Kelly; Lailatuzzahro Al-Akhda Aulia; Aizun Riski Safitri (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2026)
Academic resilience among Indonesian students remains low to moderate, and social support is widely recognized as an important protective resource. However, the strength of its association with academic resilience may vary depending on students’ internal capacities. Prior work has largely cast self-regulation as a mediator, leaving its potential moderating role in the social support–academic resilience link underexamined, particularly in Indonesian samples. This study examined that association and tested whether self-regulation moderates it. Using an explanatory correlational design, we surveyed 220 students in Pasuruan, East Java, recruited through purposive sampling, with data collected online via three adapted instruments: the Academic Resilience Scale (ARS-30; α = .80), the Multidimensional Scale of Perceived Social Support (MSPSS; α = .82), and the Self-Regulated Learning Questionnaire (SRLQ; α = .85). Data were analyzed using moderated regression analysis with mean-centered predictors. Social support was a significant positive predictor of academic resilience (R² = .525, p < .001). Self-regulation added a small independent contribution (ΔR² = .025, p = .001), whereas the social support × self-regulation interaction added a substantially larger one (ΔR² = .095, p < .001). Simple slopes analysis revealed that the positive association between social support and academic resilience was strongest among students with low self-regulation and became weaker as self-regulation increased. These findings indicate that self-regulation functions as a compensatory internal resource that reduces students’ reliance on social support in maintaining academic resilience. The study highlights the importance of strengthening both supportive educational environments and students’ self-regulatory capacities to promote academic resilience in higher education